The Assistance of Santri in Processing Snack Plastic Waste into Colleges and Photo Sketches in Female Pesantren - Ekaningsih, Lely Ana Ferawati; S.A.P., Rangga Sa’adillah; Aini, Aula Izatul; Novitasari, Diana; Khafidhoh, Aulia (Proceedings of Annual Conference on Community Engagement, 2022)
Starting from the negative stigma of society about pesantren as a slum place and a lot of garbage scattered, this assistance was carried out warding off that stigma. Santri as assisted subjects were chosen as agents of change to initiate and process waste into more useful things. The assistance to santri is carried out to process plastic waste into two products that are worth selling, namely collages and photo sketches. Through the ABCD (Asset-Based Community Development) mentoring approach using three steps of mentoring, namely pre, process, and post-assistance, this resulted in findings of a positive impact on the pesantren environment to deal with scattered piles of garbage.